Analyzing Public Sector Marketing in China: A case Study from Anhui Province, China. - Zaheer, Ahmad Nawaz (Advances in Social Sciences Research Journal, 2015)
The potential of public sector marketing in boosting organization’s efficiency and service quality has rarely been emphasized. Although, services provision for general public is considered important in Chinese organization, the characteristics of marketing outcome in bringing customers satisfaction by public sector is not yet fully understood. This study has analyzed the effectiveness of public services marketing in delivering the quality services to general public by taking into account the opinion of mangers running a public sector organization about the way they hold marketing factors as a strategic aim. We also documented the performance level of organizations from Hefei and Wuhu cities of Anhui province of China in order to identify significant factors governing marketing outcomes. Results of General Linear Model revealed that knowledge and skill is considered an important ingredient for raising the performance level of organizations in both cities. In addition, managers of public sectors have adopted marketing information and resources as key parameters while defining their strategies during marketing. The target population i.e. general population of these two cities has overwhelmingly benefited from services extended by public sectors mainly due to effective marketing outcomes. This study concludes that public sector marketing in China has been an effective tool because of its foundation being laid on key ingredients such as information, resource utilization, knowledge and skills.